Photoelectric building material and preparation method thereof

By using chemical vapor deposition method to prepare perovskite light absorbing layers on building material substrates with higher roughness, the problem of single perovskite photovoltaic building materials substrates and difficult to prepare thin film batteries is solved, and the types of photovoltaic building materials are broadened, cost reduction and service life of photovoltaic building materials are achieved.

CN119677296APending Publication Date: 2025-03-21WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411716897.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing perovskite photovoltaic building materials have a single substrate, making it difficult to prepare thin film batteries on substrates with higher roughness, and the energy usage and carbon emissions of photovoltaic glass building materials are relatively high.

Method used

Using building materials with a surface roughness of microns as the substrate, a perovskite absorbing layer is prepared by chemical vapor deposition, and a special-shaped photovoltaic film is prepared on the rough substrate with the cooperation of other layers.

Benefits of technology

It has effectively broadened the types and use scope of photovoltaic building materials, reduced production costs, increased light utilization and service life, and promoted the industrialization process of thin-film photovoltaic building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677296A_ABST
    Figure CN119677296A_ABST
Patent Text Reader

Abstract

The invention relates to a photoelectric building material and a preparation method thereof. The photoelectric building material comprises a substrate and a perovskite device arranged on the substrate, the perovskite device comprises a bottom transparent electrode layer, a first charge transport layer, a perovskite light absorption layer, a second charge transport layer and a top transparent electrode layer which are sequentially laminated on the substrate from bottom to top. The substrate is made of a building material with micron-sized surface roughness; the perovskite light absorption layer is obtained by performing chemical vapor deposition on organic ammonium salt steam and the CsYPbXCsY sandwich structure substrate, wherein X and Y are halogens. According to the invention, the rough building material is used as the substrate, the perovskite light absorption layer is prepared through a chemical vapor deposition method, and the special-shaped photovoltaic film is prepared on the rough substrate under the cooperation of other layers of the perovskite device, so that the variety and the application range of photovoltaic building materials are effectively widened; precious metal materials are not needed, production cost is saved, and service life can be prolonged; the preparation method is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photovoltaic building integration, and in particular to a photovoltaic building material and a preparation method thereof. Background Art

[0002] As energy conservation and emission reduction become a global consensus, the development of low-energy green building materials that can meet the power generation needs while taking into account the basic functions and aesthetic requirements of buildings has become an inevitable trend for future development. Lightweight and efficient thin-film solar cells can be integrated into traditional building materials to construct a new type of photovoltaic building integrated materials. As a photovoltaic building material, perovskite thin films with low prices, high photoelectric conversion efficiency, good weak light performance and customizable patterns show great potential in the field of photovoltaic building integration.

[0003] At present, perovskite thin film building materials mainly use photovoltaic glass as the substrate, and then use a layer of photovoltaic glass to encapsulate the surface, and then install it on the surface of the building for power generation curtain wall or photovoltaic tile. However, due to the low strength and fragility of glass, its life span is much shorter than the service life of the building. In addition, the energy consumption and carbon emissions of photovoltaic glass building materials are much higher than those of opaque building materials.

[0004] Using more building materials, such as ceramic wall panels with a roughness of micrometers, engineering plastics of polyvinyl fluoride or polycarbonate, and stainless steel plates as substrates to directly deposit photovoltaic thin films, the rough surface can serve as a natural anti-reflection layer to increase light utilization, which can not only broaden the types and scope of use of photovoltaic building materials, enhance the service life of photovoltaic building materials, but also have great potential for building energy conservation. However, unlike the smooth glass substrate most commonly used for perovskite thin-film cells, the surface roughness of these building materials can reach more than ten micrometers, and the surface peaks and valleys are irregular, making it very difficult to directly prepare special-shaped thin-film cells on their surfaces; in addition, unlike transparent glass-based perovskite building materials where light is incident from the back, traditional building materials are usually opaque, and light needs to be incident from the front, so opaque precious metal electrodes such as gold, silver, and copper cannot be used; in summary, it is crucial to develop a new type of perovskite photovoltaic building material and its preparation process. Summary of the invention

[0005] The purpose of the present invention is to overcome the above technical deficiencies, provide a photovoltaic building material and a preparation method thereof, and solve the technical problems in the prior art that the perovskite photovoltaic building material substrate is single and it is difficult to prepare thin-film batteries on a substrate with high roughness.

[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a photovoltaic building material, comprising a substrate, and a perovskite device arranged on the substrate; the perovskite device comprises a bottom transparent electrode layer, a first charge transport layer, a perovskite light absorbing layer, a second charge transport layer and a top transparent electrode layer stacked in sequence from bottom to top on the substrate; the substrate is a building material with a surface roughness of micrometer level; the perovskite light absorbing layer is obtained by chemical vapor deposition of organic ammonium salt vapor and a CsY|PbX|CsY sandwich structure substrate, wherein X and Y are halogens.

[0007] In a second aspect, the present invention provides a method for preparing a photovoltaic building material, comprising the following steps: The building material with micron-level roughness is cleaned and used as a substrate, and a bottom transparent electrode layer, a first charge transport layer, a perovskite light absorption layer, a second charge transport layer and a top transparent electrode layer are prepared on the substrate from bottom to top to obtain a photovoltaic building material.

[0008] Compared with the prior art, the beneficial effects of the present invention include: The present invention uses a relatively rough building material as a substrate, prepares a perovskite light-absorbing layer by a chemical vapor deposition method, and then with the cooperation of other layers of the perovskite device, realizes the preparation of a special-shaped photovoltaic film on a rough substrate, and the roughness is from the micron level of the substrate to the nanometer level of the final photovoltaic building material, effectively broadening the types and scope of use of photovoltaic building materials; and adopts a CsY|PbX|CsY sandwich structure substrate structure, which is more conducive to improving the uniformity of ion diffusion distribution in the device; and the bottom electrode and the top electrode are both transparent, and the frontal incidence of light can be realized, without the need for opaque precious metal materials, saving production costs, and with the cooperation of the rough substrate, reducing light reflection, increasing light utilization, and increasing the service life of the material of the present invention. The preparation method of the present invention is simple and has the conditions for high-throughput preparation, which helps to promote the industrialization process of thin-film photovoltaic building materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 is the confocal microscope morphology of the sample in Example 1 of the present invention; wherein, (a) a ceramic plate, (b) a perovskite device deposited on the ceramic plate; Figure 2 This is a physical picture of the pin-type power generation ceramic plate assembly in Example 4. DETAILED DESCRIPTION

[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0011] The integrated photovoltaic building materials reported so far generally require the use of double-layer glass components superimposed and installed on the surface of the original building materials, which not only has a small application range but also causes serious waste. In order to expand the building's ability to utilize solar energy, broaden the types and application range of photovoltaic building materials, and overcome the defects of the traditional perovskite photovoltaic building material substrate being single and the difficulty in preparing thin-film batteries on a substrate with high roughness, the present invention provides a photovoltaic building material and its preparation method and application.

[0012] In a first aspect, the present invention provides a photovoltaic building material, comprising a substrate, and a perovskite device arranged on the substrate; the perovskite device comprises a bottom transparent electrode layer, a first charge transport layer, a perovskite light absorbing layer, a second charge transport layer and a top transparent electrode layer stacked in sequence from bottom to top on the substrate; the substrate is a building material with a surface roughness of micrometer level; the perovskite light absorbing layer is obtained by chemical vapor deposition of organic ammonium salt vapor and a CsY|PbX|CsY sandwich structure substrate, wherein X and Y are halogens.

[0013] Preferably, the building material includes a ceramic plate, an engineering plastic plate, an enamel plate or a decorative stainless steel plate, and the roughness is below 10 μm.

[0014] Further preferably, the material of the engineering plastic board includes polyvinyl fluoride or polycarbonate; ceramic boards, engineering plastic boards, etc. can be used as wall panels.

[0015] Preferably, the bottom transparent electrode layer is prepared by magnetron sputtering and has a thickness greater than 200 nm.

[0016] Further preferably, the bottom transparent electrode layer includes an indium tin oxide layer, an indium zinc oxide layer or an indium tungsten oxide layer; the thickness of the bottom transparent electrode layer is 250 to 500 nm. In the present invention, by controlling the thickness of the bottom transparent electrode layer, good conductivity is ensured while taking into account cost and production efficiency.

[0017] Further preferably, the bottom transparent electrode layer (TCO) is prepared by radio frequency power magnetron sputtering, the target material is indium tin oxide (ITO), indium zinc oxide (IZO) or indium tungsten oxide (IWO), and the sputtering power is 35 to 90 W.

[0018] Preferably, the perovskite light absorbing layer is Cs x FA 1-x PbI 3(1-x) Br 3x layer with a thickness of 400 to 800 nm.

[0019] Further preferably, Cs x FA 1-x PbI 3(1-x) Br 3xThe layer is obtained by two-step vapor deposition, and the specific preparation steps include: firstly, thermally evaporating a first inorganic precursor containing Cs, a second inorganic precursor containing Pb, and a third inorganic precursor containing Cs (CsY|PbX|CsY) in sequence to prepare a sandwich structure substrate; then, the organic ammonium salt film (FAX|MAY, formamidine halide|methyl ammonium halide) sprayed on the glass cover is vaporized at 160-180°C and 80-120Pa, and chemically vapor deposited with the sandwich structure substrate to obtain Cs x FA 1-x PbI 3(1-x) Br 3x wherein X and Y are independently selected from Cl, Br or I.

[0020] Further preferably, the thickness of the first inorganic precursor and the third inorganic precursor is 10-50 nm, and the thickness of the second inorganic precursor is 300-500 nm; the organic ammonium salt film is formed by spraying an organic ammonium salt solution at 85-95° C., and the organic ammonium salt solution is obtained by dissolving FAX and MAY in ethanol at a mass ratio of (4-10):1; based on the total mass of FAX and MAY, the spray density of the ammonium salt solution on the glass cover is 5-15 mg / cm 2 .

[0021] Preferably, when the perovskite device is a pin structure (i.e., the first charge transport layer is a hole transport layer, and the second charge transport layer is an electron transport layer), the first charge transport layer is nickel oxide (NiO X ), copper phthalocyanine (CuPc), 2,2',7,7'-tetrakis(N,N-di-p-tolyl)amino-9,9-spirobifluorene (spiro-TTB), self-assembled small molecules (SAM), any one of them, with a thickness of 10 to 40 nm; the second charge transport layer is fullerene|tin oxide (C60|SnO 2 ) double electron layer, the thickness of C60 is 15-30nm, SnO 2 The thickness is 10 to 40 nm.

[0022] Further preferably, when the perovskite device is a pin structure, the first charge transport layer is prepared by any one of thermal evaporation, ultrasonic spray, radio frequency power magnetron sputtering, electron beam deposition or spraying, and annealed at 200-500 ° C for 20-40 min; in the second charge transport layer, the preparation method of C60 is thermal evaporation, and the thermal evaporation rate is 0.1-0.2 A / s (angstrom / second); SnO 2 The preparation method is atomic layer deposition (ALD), ALD SnO 2 The growth rate is 0.1-0.15 A / cycle, and the growth temperature is 100-200 °C.

[0023] In the present invention, C60|SnO 2 Double electron layer, where SnO 2 It plays a certain blocking role.

[0024] Preferably, when the perovskite device is a nip structure (i.e., the first charge transport layer is an electron transport layer, and the second charge transport layer is a hole transport layer), the first charge transport layer is tin oxide (SnO 2 ), titanium oxide (TiO 2 ) or zinc oxide (ZnO 2 ) with a thickness of 10 to 40 nm; the second charge transport layer is 2,2",7,7"-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD)|molybdenum oxide (MoO X ), wherein the thickness of spiro-OMeTAD is 50-200 nm, and the thickness of molybdenum oxide is 5-15 nm. Molybdenum oxide can be used as a barrier layer.

[0025] Further preferably, when the perovskite device is a nip structure, the preparation method of the first charge transport layer adopts any one of RF power magnetron sputtering, atomic layer deposition or chemical bath deposition, the power of RF power magnetron sputtering is 35 to 90 W, and the thickness is 20 to 40 nm; SnO in atomic layer deposition (ALD) 2 The growth rate is 0.3-0.7 A / cycle and the thickness is 10-40 nm.

[0026] Further preferably, when the photovoltaic building material is a nip structure, in the second charge transport layer, the preparation method of spiro-OMeTAD is slit coating printing, the slit coating precursor solvent is a 6:4 chlorobenzene / ethyl acetate mixed solvent, the solution concentration is 18-22 mg / mL, and the printing speed is 6-8 mm / s; the preparation method of molybdenum oxide is thermal evaporation, and the thermal evaporation rate is 0.1-0.2 A / s.

[0027] Preferably, the top transparent electrode layer includes an indium tin oxide layer, an indium zinc oxide layer or an indium tungsten oxide layer; and the thickness of the top transparent electrode layer is 100-200 nm.

[0028] Further preferably, the top transparent electrode layer is prepared by two-step RF power magnetron sputtering, the target material is indium tin oxide (ITO), indium zinc oxide (IZO) or indium tungsten oxide (IWO), the first step is to deposit 15 to 25 nm with 30 to 40 W power, and the second step is to deposit 80 to 100 nm with 75 to 90 W. The present invention first uses low-power sputtering to reduce sputtering damage to other functional layers such as ALD tin oxide layer or spiro layer.

[0029] In a second aspect, the present invention provides a method for preparing a photovoltaic building material, comprising the following steps: The building material with micron-level roughness is cleaned and used as a substrate, and a bottom transparent electrode layer, a first charge transport layer, a perovskite light absorption layer, a second charge transport layer and a top transparent electrode layer are prepared on the substrate from bottom to top to obtain a photovoltaic building material.

[0030] Preferably, in the present invention, an interface modification layer may be provided in the perovskite device according to circumstances, for example, provided between the charge transport layer and the perovskite light absorbing layer, to play a role of passivation.

[0031] Further preferably, the transparent electrode layer is prepared by magnetron sputtering, the charge transport layer is prepared by magnetron sputtering, spraying, thermal evaporation, slit coating, ultrasonic spraying, atomic layer deposition, chemical bath deposition, or electron beam deposition, the interface modification layer is prepared by printing, and the perovskite layer is prepared by vapor deposition.

[0032] The advantages of the present invention are: (1) The present invention explores a photovoltaic building material and a preparation method thereof, selects a building material with less energy consumption, more traditional and longer life as a substrate, solves the problem that the existing perovskite photovoltaic building material substrate is single and the production process is not suitable for large-scale production. It can not only broaden the types of perovskite photovoltaic building material substrates and reduce production costs, but also solve technical problems such as the difficulty of industrial production of perovskite photovoltaic building materials, which is conducive to promotion to other photovoltaic device fields and expands the types of photovoltaic building materials other than photovoltaic glass; (2) The present invention uses a relatively rough building material as a substrate, prepares a perovskite light-absorbing layer by chemical vapor deposition, and then realizes the preparation of a special-shaped photovoltaic film on a rough substrate with the cooperation of other layers of the perovskite device; and adopts a CsY|PbX|CsY sandwich structure substrate structure, which is more conducive to improving the uniformity of ion diffusion distribution in the device; (3) The bottom electrode and the top electrode of the present invention are both transparent electrodes, which can realize the frontal incidence of light, and do not require opaque precious metal materials, saving production costs. The rough substrate can serve as a natural anti-reflection layer, increasing the light utilization rate and extending the service life of photovoltaic building materials; (4) The present invention provides a thin-film photovoltaic device prepared by a fully industrialized process, and the perovskite light-absorbing film can be designed according to the requirements of the building substrate to meet aesthetic needs; the production process provided by the present invention simplifies the production process and production cost of perovskite photovoltaic building materials, which helps to promote the industrialization of thin-film photovoltaic building materials.

[0033] Therefore, the present invention overcomes the difficulty of preparing special-shaped photovoltaic films on rough substrates, and uses a fully industrializable process to prepare photovoltaic building materials that can generate electricity, thereby broadening the types of photovoltaic building materials. In addition, transparent conductive oxides are used as electrodes, and opaque precious metal materials are not introduced, saving production costs. Moreover, due to the semi-transparent characteristics of the battery, the color and pattern can be adjusted according to the requirements of the building material substrate, fully meeting the architectural function and aesthetic requirements.

[0034] The present invention is further described in detail below with reference to specific embodiments.

[0035] Example 1 A method for preparing a PIN type photovoltaic building material comprises the following steps: (1) A ceramic plate with a roughness of micrometers was used as a battery substrate. The ceramic plate was cut into small pieces of 2.5 cm × 2.5 cm using a grinding wheel cutter. The pieces were then ultrasonically cleaned in detergent, deionized water, and anhydrous ethanol for 20 minutes each. (2) Using 85 W of power, a 300 nm thick indium tin oxide transparent electrode was magnetron sputtered on a clean ceramic plate using an RF power supply. (3) A 30 nm nickel oxide layer was magnetron sputtered on the bottom transparent electrode using a radio frequency power supply at a power of 30 W and annealed at 250 °C for 30 min to obtain a hole transport layer; (4) 15 nm cesium bromide, 350 nm lead iodide, and 15 nm cesium bromide were sequentially deposited on the hole transport layer by physical vapor deposition (specifically thermal evaporation) to prepare a sandwich structure substrate, and FAI:FACl = 4:1 (spraying density of 10 mg / cm 2 ) is placed on the sandwich structure substrate, with the cover plate and the substrate kept at a distance of 200 μm, and reacted at 180 °C for 5 min to obtain a 600 nm thick perovskite light-absorbing layer; (5) A 20 nm electron transport layer C60 was deposited on the perovskite light absorbing layer using 0.15 A / s thermal evaporation; then 15 nm SnO was deposited using ALD 2 , the growth rate was 0.12 A / cycle, and a double-layer electron transport layer was obtained; (6) Finally, in SnO 2 The effective area of ​​the layer preparation is 0.25 cm 2 The 100 nm indium tin oxide top transparent electrode is first deposited with 20 nm using 35 W power, and then 80 nm is deposited with 80 W to obtain a pin-type optoelectronic building material.

[0036] Confocal microscopy morphology of perovskite devices before and after deposition on ceramic plates Figure 1As shown, the roughness of the ceramic plate is 6.5 μm. After the perovskite device is prepared by the method of the present invention, the surface roughness is significantly reduced to 2.1 μm, and the roughness is reduced by 3 times, which fully proves the full coverage of the rough substrate by the method of the present invention.

[0037] Example 2 A method for preparing a NIP type photovoltaic building material, the steps are as follows: (1) A ceramic plate with a roughness of micrometers was used as a battery substrate. The ceramic plate was cut into small pieces of 2.5 cm × 2.5 cm using a grinding wheel cutter. The pieces were then ultrasonically cleaned in detergent, deionized water, and anhydrous ethanol for 20 minutes each. (2) Using 85 W of power, a 300 nm thick indium tin oxide transparent electrode was magnetron sputtered on a clean ceramic plate using an RF power supply. (3) A 30 nm tin oxide layer was grown on the bottom transparent electrode using atomic layer deposition technology at a growth rate of 0.5 A / cycle and annealed at 170 °C for 30 min to obtain an electron transport layer; (4) 15 nm cesium bromide, 350 nm lead iodide and 15 nm cesium bromide were sequentially deposited on the electron transport layer by physical vapor deposition to prepare a sandwich structure substrate. A cover plate sprayed with FAI:FACl=4:1 was placed on the lead iodide sandwich structure substrate. The cover plate and the substrate were kept 200 μm apart. The reaction was carried out at 180 °C for 5 min to obtain a 600 nm thick perovskite light-absorbing layer. (5) Slit-coating spiro-OMeTAD as a hole transport layer on the perovskite light-absorbing layer. The slit-coating precursor solvent is a 6:4 chlorobenzene / ethyl acetate mixed solvent with a solution concentration of 20 mg / mL and a printing speed of 7 mm / s. (6) Thermally evaporate 9 nm molybdenum oxide as a barrier layer on the hole transport layer at a thermal evaporation rate of 0.1-0.2 A / s; (7) The final effective area is 0.25 cm 2 The 100 nm indium tin oxide top transparent electrode was first deposited with 20 nm using 35 W power, and then with 80 W to obtain the nip-type optoelectronic building material.

[0038] The active area of ​​the cell is 0.25 cm 2 , the simulated sunlight intensity is 100 mW cm -2 , that is, the photoelectric conversion efficiency was tested under one sunlight. The test results showed that the obtained nip photovoltaic building material (small area power generation ceramic plate) can output 0.50 V voltage and 2.2 mA current.

[0039] Example 3 A method for preparing a nip-type photovoltaic building material is different from Example 2 only in that a stainless steel sheet with a roughness of micrometer level is used as a battery substrate, and other steps and conditions are the same as those of Example 2.

[0040] The active area of ​​the cell is 0.25 cm 2 , the simulated sunlight intensity is 100 mW cm -2 , that is, the photoelectric conversion efficiency was tested under one sunlight. The test results showed that the obtained nip-type photovoltaic building material (small-area power generation stainless steel sheet) can output 0.68 V voltage and 2.5 mA current.

[0041] Example 4 A method for preparing a PIN type photovoltaic building material, comprising the following steps: (1) A 10 cm × 10 cm stainless steel plate was used as the battery substrate and ultrasonically cleaned in detergent, deionized water, and anhydrous ethanol for 20 minutes each; (2) Use 0.1 mm high temperature tape to divide a 10 cm × 10 cm stainless steel plate into 10 regions with a width of 8 mm, namely P1, and use 85 W of radio frequency power supply magnetron sputtering to deposit a 300 nm indium tin oxide bottom transparent electrode on the stainless steel plate; (3) Remove the high-temperature tape of P1, and stick a 0.1 mm high-temperature tape near the top of P1 to form P2. Then, magnetron sputter a 30 nm nickel oxide layer on the bottom transparent electrode using a radio frequency power supply at a power of 30 W, and anneal at 250 °C for 30 min to obtain a hole transport layer. (4) On the hole transport layer, 15 nm cesium bromide, 350 nm lead iodide and 15 nm cesium bromide were sequentially deposited by physical vapor phase to prepare a sandwich structure substrate. A cover plate sprayed with FAI:FACl=4:1 was placed on the lead iodide sandwich structure substrate. The cover plate and the substrate were kept 200 μm apart. The reaction was carried out at 180 °C for 5 min to obtain a 600 nm thick perovskite light-absorbing layer. (5) A 20 nm electron transport layer C60 was deposited on the perovskite light absorbing layer using 0.15 A / s thermal evaporation; then 15 nm SnO was deposited using ALD 2 , the growth rate is 0.12 A / cycle; (6) Remove the P2 high temperature tape and apply a 0.1 mm high temperature tape on the surface close to P2, i.e. P3, and then 2 A 100 nm indium tin oxide top transparent electrode is magnetron sputtered on the layer using a radio frequency power supply. First, 20 nm is deposited using a power of 35 W, and then 80 nm is deposited using a power of 80 W to obtain a series-type pin-type photovoltaic building material (photovoltaic stainless steel plate).

[0042] It is understandable that the above-mentioned P1-P3 lines are routine operations for making series battery assemblies. Due to the use of a rough bottom, traditional laser cutting will cut into other functional layers, so manual operation or a homemade mask is preferred.

[0043] The obtained PIN type photovoltaic building material product is shown in the figure Figure 2 As shown in the figure, a small LED bulb is added to the photovoltaic stainless steel plate as a load using copper conductive glue. The effective area of ​​the battery is 50 cm 2 , the simulated sunlight intensity is 100 mW cm -2 , that is, the photoelectric conversion efficiency test was carried out under the irradiation of one sun. The test results showed that the power generation stainless steel plate was 100 mW / cm 2 Under sunlight, it can output 5.71 V voltage and 38 mA current. The LED bulb is 5 mW / cm 2 It can also emit light under extremely weak light conditions.

[0044] Example 5 A method for preparing a NIP type photovoltaic building material, which differs from Example 2 only in that the raw material ratio of the ammonium salt solution is different during the preparation of the perovskite light absorbing layer, and the other steps and conditions are the same as Example 2. The specific differences are: 15 nm cesium iodide, 350 nm lead iodide and 15 nm cesium iodide were deposited in sequence by physical vapor deposition to prepare the inorganic precursor into a sandwich structure. A cover plate sprayed with FAI:FABr=10:1 was placed on the lead iodide substrate and reacted at 180 °C for 5 min to obtain a 600 nm thick perovskite light-absorbing layer.

[0045] The active area of ​​the cell is 0.25 cm 2 , the simulated sunlight intensity is 100 mW cm -2 , that is, the photoelectric conversion efficiency was tested under one sunlight. The test results showed that the obtained nip photovoltaic building material (small area power generation ceramic plate) can output 0.56 V voltage and 3.1 mA current.

[0046] Example 6 A method for preparing a nip-type photovoltaic building material, which differs from Example 2 only in that the thickness of the transparent indium tin oxide bottom electrode deposited is 200, 300, 400, and 500 nm respectively, and the other steps are the same as Example 2. The effective area of ​​the battery is 0.25 cm 2 , the simulated sunlight intensity is 100 mW cm -2 , that is, the photoelectric conversion efficiency test is carried out under the irradiation of one sun. The test results of the obtained NIP type photovoltaic building material are shown in Table 1 below.

[0047] Table 1 Test results of nip type photovoltaic building materials obtained in Example 6

[0048] According to the test results in Table 1, when the bottom transparent electrode is 200 nm, the electrode does not completely cover the micron-level rough substrate, resulting in almost no battery current and a short circuit. When the transparent electrode thickness is 300-500 nm, the battery current and voltage results are not much different. In order to reduce time cost and material waste, the transparent bottom electrode thickness is preferably 300-500 nm, and more preferably 300-400 nm.

[0049] Comparative Example 1 A method for preparing a NIP type photovoltaic building material, which differs from Example 2 only in that when preparing the perovskite light absorbing layer in step (4), only 30 nm cesium bromide and 350 nm lead iodide are deposited successively, and the other steps and conditions are the same as those in Example 2.

[0050] The active area of ​​the cell is 0.25 cm 2 , the simulated sunlight intensity is 100 mW cm -2 , that is, the photoelectric conversion efficiency test is carried out under the irradiation of one sun. The test shows that the obtained nip photovoltaic building material (small area power generation ceramic plate) can output 0.35 V voltage and 1.8 mA current; this shows that in the preparation process of the perovskite light absorption layer of the present invention, it is more advantageous to use a sandwich structure substrate.

[0051] Comparative Example 2 A method for preparing a NIP type photovoltaic building material, which differs from Example 2 only in that when preparing the perovskite light absorbing layer in step (4), only 350 nm lead iodide and 30 nm cesium bromide are deposited successively, and the other steps and conditions are the same as those in Example 2.

[0052] The active area of ​​the cell is 0.25 cm 2 , the simulated sunlight intensity is 100 mW cm -2 , that is, the photoelectric conversion efficiency test is carried out under the irradiation of one sun. The test shows that the obtained nip photovoltaic building material (small area power generation ceramic plate) can output 0.22 V voltage and 1.5 mA current; this shows that in the preparation process of the perovskite light absorption layer of the present invention, it is more advantageous to use a sandwich structure substrate.

[0053] In summary, the photovoltaic building materials of the present invention are prepared using a fully industrialized process, and the substrate can use building materials with a certain degree of roughness, which effectively broadens the types of substrates and reduces costs; and the color and pattern can be customized. The building materials can not only generate electricity and reduce building energy consumption, but also meet the aesthetic needs of the building. Moreover, no precious metal materials are introduced in the production process, which greatly reduces the production cost of photovoltaic building materials.

[0054] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A photovoltaic building material, characterized in that: It includes a substrate and a perovskite device arranged on the substrate; the perovskite device includes a bottom transparent electrode layer, a first charge transport layer, a perovskite light absorption layer, a second charge transport layer and a top transparent electrode layer which are sequentially stacked from bottom to top on the substrate; The substrate is a building material with a surface roughness of micrometer level; The perovskite light-absorbing layer is obtained by chemical vapor deposition of organic ammonium salt vapor and a CsY|PbX|CsY sandwich structure substrate, wherein X and Y are halogens.

2. The photovoltaic building material according to claim 1, characterized in that: The building materials include ceramic plates, engineering plastic plates, enamel plates or decorative stainless steel plates.

3. The photovoltaic building material according to claim 1, characterized in that: The bottom transparent electrode layer is prepared by magnetron sputtering and has a thickness greater than 200 nm, and the target material includes indium tin oxide, indium zinc oxide or indium tungsten oxide; The top transparent electrode layer is prepared by two-step radio frequency power magnetron sputtering, and the target material includes indium tin oxide, indium zinc oxide or indium tungsten oxide; the thickness of the top transparent electrode layer is 100-200 nm.

4. The photovoltaic building material according to claim 1, characterized in that: The thickness of the perovskite light absorbing layer is 400-800 nm; The perovskite light-absorbing layer is obtained by vapor deposition in two steps, and the specific preparation steps include: First, a first inorganic precursor containing Cs, a second inorganic precursor containing Pb and a third inorganic precursor containing Cs are sequentially thermally evaporated to prepare the CsY|PbX|CsY sandwich structure substrate; then, organic ammonium salt vapor and the sandwich structure substrate are chemically vapor deposited to obtain a perovskite light-absorbing layer.

5. The photovoltaic building material according to claim 4, characterized in that: The first inorganic precursor and the third inorganic precursor are deposited to a thickness of 10 to 50 nm, and the second inorganic precursor is deposited to a thickness of 300 to 500 nm; The first inorganic precursor is CsY, the second inorganic precursor is PbX, and the third inorganic precursor is CsY; the organic ammonium salt vapor is obtained by vaporizing the organic ammonium salt film sprayed on the glass cover plate at 160°C to 180°C and 80 to 120 Pa; wherein the organic ammonium salt film is formed by spraying an organic ammonium salt solution obtained by dissolving FAX and MAY in ethanol at a mass ratio of (4 to 10):1, wherein X and Y are independently selected from Cl, Br or I; based on the total mass of FAX and MAY, the spraying density is 5 to 15 mg / cm 2 .

6. The photovoltaic building material according to claim 1, characterized in that: When the perovskite device is a pin structure, The first charge transport layer is any one of nickel oxide, copper phthalocyanine, 2,2',7,7'-tetrakis(N,N-di-p-tolyl)amino-9,9-spirobifluorene, and self-assembled small molecules, and has a thickness of 10 to 40 nm; The second charge transport layer is a C60|SnO2 double electron layer, wherein the thickness of C60 is 15 to 30 nm, and the thickness of SnO2 is 10 to 40 nm.

7. The photovoltaic building material according to claim 6, characterized in that: When the perovskite device is a pin structure, The first charge transport layer is prepared by any one of thermal evaporation, ultrasonic spraying, radio frequency power magnetron sputtering, electron beam deposition or spraying, and annealed at 200-500° C. for 20-40 min; In the second charge transport layer, C60 is prepared by thermal evaporation at a rate of 0.1 to 0.2 A / s; SnO2 is prepared by atomic layer deposition at a growth rate of 0.1 to 0.15 A / cycle at a growth temperature of 100 to 200 °C.

8. The photovoltaic building material according to claim 1, characterized in that: When the perovskite device is a nip structure, The first charge transport layer is any one of tin oxide, titanium oxide or zinc oxide, and has a thickness of 10 to 40 nm; The second charge transport layer is a spiro-OMeTAD|molybdenum oxide double layer, the thickness of the spiro-OMeTAD is 50-200 nm, and the thickness of the molybdenum oxide is 5-15 nm.

9. The photovoltaic building material according to claim 8, characterized in that: When the perovskite device is a nip structure, The first charge transport layer is prepared by any one of radio frequency power magnetron sputtering, atomic layer deposition or chemical bath deposition; In the second charge transport layer, the preparation method of spiro-OMeTAD is slit coating printing; the preparation method of molybdenum oxide is thermal evaporation, and the thermal evaporation rate is 0.1 to 0.2 A / s.

10. The method for preparing a photovoltaic building material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The building material with micron-level roughness is cleaned and used as a substrate, and a bottom transparent electrode layer, a first charge transport layer, a perovskite light absorption layer, a second charge transport layer and a top transparent electrode layer are prepared on the substrate from bottom to top to obtain a photovoltaic building material.